Implementation of the Wadiah Savings Contract in BMT Fajar Bandar Lampung - Pipit Susanti; Abizar; Mawardi (ProBisnis : Jurnal Manajemen, 2023)
This research aims to determine the implementation of wadiah contracts in wadiah savings products carried out at BMT Fajar Bandar Lampung in their management and what factors are contained in these savings products. This research uses a qualitative type of research, a descriptive approach. Descriptive qualitative is a method used to dissect a phenomenon in the field. Qualitative method Descriptive is a method that describes and describes findings in the field. Qualitative method Descriptive simply describes a situation or event. Descriptive qualitative is research that focuses on problems as they exist when the research is carried out. The results of the research that has been carried out can be concluded that the implementation of the wadiah savings contract at BMT Fajar can be said to be in accordance with sharia and the procedures carried out have been carried out very well. And there are several factors in wadiah savings such as supporting factors, obstacles and strengths in managing wadiah savings products at BMT Fajar Bandar Lampung.